Wetting Control in the Layered Polymer-silver Thin Film via Femtosecond Laser Microstructuring - Umanskaya, Sofia Filippovna; Danilov, Pavel Aleksandrovich; Kudryashov, Seigey Ivanovich; Rudenko, Andrey Andreevich; Ionin, Andrey Alekseevich (Communications in Physics, 2019)
Water wetting of a structured multi-layered thin film consisting of bottom silver and top polymer layers microstructured by femtosecond laser pulses was studied. The periodic trenches were ablatively produced on the top polymer layer of the film using 515-nm, 220-fs pulses of an ytterbium-doped fiber laser at different pulse energies and the repetition rate of 20 kHz. The topography of the structured film was observed by means of a JEOL 7001F scanning electron microscope and its water wetting angles were measured by side-view microscopic imaging. The wetting angle on the microstructured surface was 144°, comparing to 83° at the raw unstructured surface of the film